2018
DOI: 10.1002/adom.201801270
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Second Harmonic Generation from WS2 Monolayers by Cooperating with Dielectric Microspheres

Abstract: Herein, a 20‐fold enhancement of the optical second harmonic generation (SHG) from WS2 monolayers by cooperating with SiO2 dielectric microspheres (MSs) is reported. Detailed experiment and simulation studies indicate that the SHG enhancement is dominantly originated by the enhanced excitation intensity and enlarged collection efficiency produced by the SiO2 MSs. The size effect of the SiO2 MS on the SHG enhancement is also systematically investigated. Moreover, the SHG enhancement is found to be very sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…[8,9]. For instance, SHG is a very sensitive and non-destructive technique for several applications in various fields, such as crystal structural detection, cancer cell diagnostics, optical switches in nano-devices [10,11,12,13,14,15]. Previous studies have demonstrated highly efficient SHG in different semi-conductor nanomaterials, such as CdS, GaAs, ZnO [16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. For instance, SHG is a very sensitive and non-destructive technique for several applications in various fields, such as crystal structural detection, cancer cell diagnostics, optical switches in nano-devices [10,11,12,13,14,15]. Previous studies have demonstrated highly efficient SHG in different semi-conductor nanomaterials, such as CdS, GaAs, ZnO [16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…We estimate about 1 million counts per second total emission from a single neutral C defect based on radiative lifetime and estimated collection efficiency (19.1% in Ref. 43 ) which can be readily observed. The coherent ZPL emission would be in the order of 2500 counts per second which is still observable.…”
Section: Resultsmentioning
confidence: 99%
“…2f , were much smaller than those of f 1 . The total enhancement factor f of the lipidic microlenses can then be calculated by f = f 1 × f 2 42 , and the results are presented by the red dots in Fig. 2f .…”
Section: Resultsmentioning
confidence: 99%